(untitled) (People and Technology Management Journal, 2017)
This article is a product of the research whose purpose was to identify the aspects of theculture of innovation in the management of universities of the Santa Marta District. Themethodology used was under the positivist paradigm, non-experimental, transectional, descriptive and field research. The finite population consisted of 37 employees. As a tool for data collection, a questionnaire was developed using the categories of 12-item Likert responses. The reliability of the instrument was determined by Cronbach's Alpha method with 0.96 reliability. The results of this research indicate that it is possible torecognized innovative employees. It is concluded that management allows employees to develop their leadership capacity. To strengthen the presence of aspects of the innovation culture that increase organizational learning is recommended.